Effects of Vermicompost and Vermiwash on the Exo-morphological Features of Common Bean (Phaseolus vulgaris L.) Plants - Rahman, Imdadur; Das, Ranangini; Gogoi, Sujata Songhalee (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The experiment was carried out during 2023-24 at the department of Life Sciences, Sibsagar University, Assam to observe the effect of the application of vermicompost and vermiwash on growth of bean plants. Vermicompost was prepared by using earthworm, Eisenia foetida. Vermiwash was prepared from the same vermibed. It was observed that throughout the experiment the bean plants grew well gradually with increasing amount of vermicompost as compared to control plants. The shoot length of common bean plant, Phaseolus vulgaris was found maximum i. e. 25.37 +1.81 cm in 700 g of vermicompost with 300 g of soil. Maximum root length of 11.93 +2.71 cm was found in the bean plants sprayed 5% vermiwash as foliar spray on the surface of the leaves. Some physico-chemical properties of the vermicompost and vermiwash were also observed. The pH of harvested vermicompost and vermiwash were found 7.27 +1.23 and 9.30 +1.21 respectively. The results of the present study clearly suggest that 700 g of vermicompost with 300 g of soil and 5% vermiwash could be used on bean plants in the near future.